Pengembangan Media Pembelajaran Berbasis Etnomatematika dalam Tradisi Nyadran pada Materi Bangun Ruang Sisi Lengkung untuk Meningkatkan Kemampuan Pemahaman Konsep - Tiara, Ellsa Winda; Harun, Lukman; Aini, Aurora Nur (Universitas PGRI Semarang, 2026)
This study aims to develop ethnomathematics-based learning media in the Nyadran tradition on the material of curved sided solids to improve students' conceptual understanding. This research is a research and development (RD) using the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The limited trial subjects were 16 grade IX students. The research instruments included expert validation sheets to measure the validity of the media, student practicality questionnaires to measure the level of practicality of the media, and pre-test and post-test questions to measure the effectiveness of the media. The results showed that the developed learning media met the criteria of very valid with a percentage of 95% based on the assessment of media experts and 91% based on the assessment of material experts. The results of the practicality test obtained a percentage of 89% with a very practical category. Meanwhile, the results of the effectiveness test showed an N-Gain value of 0.5 which is in the medium category, this indicates an increase in students' conceptual understanding after using learning media. Based on these results, ethnomathematics-based learning media in the Nyadran tradition meets the criteria of being valid, practical, and effective in improving the ability to understand mathematical concepts.